Mapping natural radioactivity of soils in the eastern Canary Islands. (January 2017) - Arnedo, M.A.; Rubiano, J.G.; Alonso, H.; Tejera, A.; González, A.; González, J.; Gil, J.M.; Rodríguez, R.; Martel, P.; Bolivar, J.P.
Abstract: The Canary Islands archipielago (Spain) comprises seven main volcanic islands and several islets that form a chain extending for around 500 km across the eastern Atlantic, between latitudes 27°N and 30°N, with its eastern edge only 100 km from the NW African coast. The administrative province of Las Palmas comprises the three eastern Canary Islands (Lanzarote, Fuerteventura and Gran Canaria). An extensive study of terrestrial gamma dose rates in surface soils has been carried out to cover the entire territory of the province (4093 km 2 ). The average outdoor gamma dose rate in air at 1 m above ground is 73 nGyh −1  at Gran Canaria, 32 nGyh −1  at Fuerteventura, and 25 nGyh −1  at Lanzarote. To complete the radiological characterization of this volcanic area, 350 soil samples at 0–5 cm depth were collected to cover all the geologic typologies of the islands. These samples were measured using high resolution gamma spectrometry to determine the activity concentrations of 226 Ra, 232 Th and 40 K. The average values obtained were 25.2 Bq/kg, 28.9 Bq/kg, and 384.4 Bq/kg, respectively. Maps of terrestrial gamma activity, effective dose, and activity concentrations of 226 Ra, 232 Th and 40 K for the region have been developed through the use of geostatistical interpolation techniques. These maps are in accord with the geology of the islands. Highlights: Terrestrial gamma dose rates to cover the territory of the eastern Canary Islands. Average outdoor gamma dose rates: 38 to 75 nGyh −1 on three islands. 350 soil samples were measured using high resolution gamma spectrometry. Averages: 226 Ra, (25.2 Bq/kg), 232 Th (28.9 Bq/kg), 40 K (384.4 Bq/kg). Radiometric maps are in accord to the geology of the islands.